1997
DOI: 10.1002/(sici)1097-0282(199705)41:6<673::aid-bip7>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of β-turns in proteins by 1-4 and 2-3 correlation model

Abstract: A 1–4 and 2–3 residue‐correlation model is proposed to predict the β‐turns in proteins. The average rate of correct prediction for the 455 β‐turn tetrapeptides and 4018 non‐β‐turn tetrapeptides in the training data base is 80.1%, and that for the 223 β‐turn tetrapeptides and 12562 non‐β‐turn tetrapeptides in the testing data base is 80.9%. Compared with the rates of correct prediction based on the residue‐independent model reported previously, the quality of prediction is significantly improved by the new mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 15 publications
0
44
0
1
Order By: Relevance
“…BC021477) was cloned into the pET28a expression vector that contains an N-terminal 6ϫ His-tag. After extensive unsuccessful crystallization trials, surface-site mutations (K141A and K142A) were made within the same construct to enhance crystallization (10)(11)(12)(13). Mutations were introduced with the QuikChange Site-Directed Mutagenesis kit (Stratagene).…”
Section: Methodsmentioning
confidence: 99%
“…BC021477) was cloned into the pET28a expression vector that contains an N-terminal 6ϫ His-tag. After extensive unsuccessful crystallization trials, surface-site mutations (K141A and K142A) were made within the same construct to enhance crystallization (10)(11)(12)(13). Mutations were introduced with the QuikChange Site-Directed Mutagenesis kit (Stratagene).…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 shows that factor score of proline (3.847) is larger than that of other amino acids; consequently, it can be concluded that the preference of proline in 7-residue fragments will difficultly lead to the formation of -turns. In the -turn prediction model developed by Zhang and Chou [18], the coupling effects between the 1st and 4th residue and the 2nd and 3rd residue were given a special consideration. When a tetrapeptide folds into a -turn (Figure 2), the interactions between the 1st and 4th residue and the 2nd and 3rd residue play an important role.…”
Section: Characteristic Analysis Of -Turnsmentioning
confidence: 99%
“…Currently, a number of outstanding -turn structure prediction methods [4,[18][19][20][21][22][23][24][25][26][27][28][29] have been developed. In the Chou-Fasman method [4], a set of probabilities was assigned to each residue and the conformational parameters and positional frequencies were determined by calculating the relative frequency of a given type of secondary structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, any predicted beta-turn type is considered as a generic beta-turn and the proposed method is compared against several related methods [13,22,23,27,43,44,[52][53][54] based on 7-fold cross validation on dataset 426, see Table 3. We note that several other beta-turn prediction methods, which are not included in our comparison, were also developed [55,56].…”
Section: Quality Of Beta-turn Vs Non-beta-turn Predictionsmentioning
confidence: 99%